Investigation of correlation study among transcutaneous and total serum bilirubin content in preterm neonates - Spandana M; Jayant Vagha; Keta Vagha (Amaltea Medical Publishing House, 2023)
Background. Neonatal jaundice is a commonly occurring problem in both full term and preterm neonates. It is one of the major causes for neonatal mortality and morbidity. Objective. To assess the correlation among transcutaneous bilirubinometer readings and Total serum bilirubin levels at different sites in early and late preterm neonates before and at the end of phototherapy. Method. An observational study was conducted in preterm neonates diagnosed with jaundice. The Transcutaneous Bilirubin (TCB) instrument, Drager JM105 is used to assess TCB and it was recorded on three sites and average of the three readings was noted. Prior to phototherapy, TCB was noted 30 min before TSB was sent. A photo-opaque patch was placed on the sternum and phototherapy was given. At the end of the phototherapy, TCB on the sternum was noted and then TSB was sent with a time gap of not more than 30 min. Results. In this study, out of 50 neonates 14 were early preterm and 36 were late preterm babies. It was found that there was a positive correlation between TCB and TSB in early preterm babies before phototherapy (p value=0.0019), but there was no correlation between TCB and TSB at the end of phototherapy. In late preterm babies there was no correlation between TCB and TSB both before phototherapy and at the end of phototherapy. Conclusion. In this study it was found that TCB has positive correlation with TSB and can be implemented for the screening of hyperbilirubinemia even in preterm neonates.